Theoretical Treatment for Properties of Surfaces and Their Interplay with Bulk Properties of Crystals. Issue 2 (30th September 2018) - Zhou, Meijuan; Springborg, Michael; Kirtman, Bernard
Abstract: It is demonstrated that there is an interconnection between surfaces, shapes, and bulk properties of macroscopic, crystalline materials. Thus, the requirement that no atom in the bulk shall experience a force from charges associated with the surface, a requirement formulated in terms of a generalized Tasker condition, leads to an interplay involving transfer of charge between different surfaces for a given sample. Through this mechanism, so‐called polar surfaces, often considered to be essentially unstable, can always be stabilized. Density functional theory slab calculations are carried out to obtain typical surface charges and associated bulk geometric displacements for an individual surface. Then the consequences of the interplay between surfaces are studied through one property that is usually considered a bulk property, namely the polarization / dipole moment per volume, and one property that is usually related to an individual surface, that is, heterogeneous catalytic activity. Model calculations illustrate the importance of charge transfer between surfaces in both cases. These calculations provide a guide for much more difficult ab initio computations that might be carried out in the future. Abstract : In this work, it is demonstrated that charge transfers between different surfaces of a crystalline sample may be necessary to stabilize the crystal structure. These transfers depend on the overall shape of the crystal and have consequences for various properties. Here, the consequences for one bulk property, that is, polarization, and for one surface property, that is, heterogeneous catalysis, are discussed.